SINTESIS PARTIKEL NANO BARIUM TITANAT MENGGUNAKAN METODE PROSES PREKURSOR DENGAN PULP MERANG SEBAGAI TEMPLAT - Bambang Sunendar P; Mery Agustina; Arie Wibowo; Evi Oktavia (Center for Pulp and Paper, 2010)
Barium titanate (BaTiO3) with perovskite tetragonal crystal structure is known as ferroelectric materials. Recently, this material is widely used in electronic industry such as sensor, transducer, infrared detector and Multi Layer Ceramic Capacitors (MLCCs) because barium titanate is more environmental friendly, the T curie of barium titanate is lower than the other dielectric materials and it has a high dielectric constant. Nanoparticle size of barium titanate is needed to improve the it’s performance. Conventional method of material synthesizing usually produces impurities from ball milling process and the particle size of material is not in nano size. This experiment, we synthesize barium titanate using precursor process method with pulp of rice straw (Oryza sativa) as a template. Variation in calcination temperature (700°C, 900°C, 1100°C) and precursor concentration (0.1 M and 0.07 M) was conducted to get information about the influence of calcination temperature and precursor concentration to the cristallinity and particle size of barium titanate. XRD result showed that barium titanante was already formed in 700ºC calcination temperature and has its optimum temperature on 900ºC. As the concequence of rising of calcination temperature, cristallinity of sample was increased. SEM images showed that particle size of sample was already in nano size. Meanwhile, as the result of decreasing of precursor concentration, the particle size of sample was decreased. Key words : barium titanate, nano particle, pulp Oryza sativa, precursor process method INTISARIBarium titanat (BaTiO3) dengan struktur kristal perovskite tetragonal telah dikenal bersifat material ferroelektrik. Material ini telah banyak digunakan dalam aplikasi di bidang elektronik seperti sensor, transducers, infrared detector dan multi layer ceramic capacitor (MLCCs). Hal ini dikarenakan barium titanat lebih ramah lingkungan, memiliki T curie yang lebih rendah daripada material dielektrik lain, dan memiliki konstanta dielektrik yang tinggi. Partikel barium titanat yang berukuran nano diperlukan untuk meningkatkan kinerjanya. Metode konvensional dalam memproses material seringkali menimbulkan pengotor yang berasal dari proses ball milling serta ukuran partikel yang didapatkan belum mencapai nano. Dalam penelitian ini, partikel titanat berukuran nano partikel disintesis dengan menggunakan metode proses prekursor dengan pulp merang (Oryza sativa) sebagai template. Variasi suhu kalsinasi (700°C, 900°C, 1100°C) dan konsentrasi prekursor (0,1 M dan 0,07 M) dilakukan untuk mengetahui pengaruh suhu kalsinasi dan konsentrasi prekursor terhadap kristalinitas dan ukuran partikel barium titanat. Hasil XRD menunjukkan bahwa pada suhu kalsinasi 700ºC barium titanat telah terbentuk dan temperatur optimum pada 900ºC. Seiring dengan peningkatan suhu kalsinasi, kristalinitas barium titanat juga meningkat. Hasil SEM menunjukkan serbuk barium titanat hasil sintesis telah berukuran nano. Dengan menurunkan konsentrasi prekursor menjadi 0,07 M, didapatkan serbuk barium titanat yang lebih kecil bila dibandingkan dengan serbuk yang disintesis menggunakan konsentrasi prekursor 0,1 M.Kata kunci : barium titanat, nano partikel, pulp Oryza sativa, metode proses prekursor